mr DOMINASI PERAN ARSITEKTUR NUSANTARA PADA BANGUNAN GEDUNG SATE BANDUNG: Kajian Kualitatif terhadap Perwujudan Arsitektur Tradisional pada Bangunan Pemerintah Kolonial Gedung Sate Bandung - muhamad, ilham; Hasibuan, Muhammad Rifa’i (Jurusan Arsitektur UPR, 2025)
Gedung Sate, located in Bandung, is a symbol of cultural acculturation, representing a blend of European colonial architecture and Nusantara architectural elements. Built in 1920 and designed by Dutch architect Johan Gerber, the building displays influences from modern European architecture, such as the Italian Renaissance, Amsterdam School, and Art Deco, combined with local elements. The presence of Nusantara architectural elements, such as traditional roof shapes and temple-style ornaments, not only serves as an aesthetic element but also plays a role in shaping the building's visual and symbolic identity. This study aims to examine the role of Nusantara architecture in shaping the character of the Gedung Sate building, particularly through the analysis of facade elements, roofs, and openings. The research method used is descriptive qualitative with a literature study approach and visual analysis of the building's architectural elements. The results of the study indicate that the integration of Nusantara architectural elements contributes significantly to the architectural character of Gedung Sate, both from a visual, symbolic, and contextual aspect to the tropical environment. Thus, Gedung Sate can be understood as a hybrid architecture that reflects a harmonious collaboration between European and Nusantara styles. This study is expected to enrich our understanding of the role of local architecture in shaping the identity of colonial buildings in Indonesia.